Conviction or convenience? conversion to Islam in the West, Korea, and Southeast Asia - Allison, Safwaan Zamakda (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
The phenomenon of religious conversion to Islam has grown steadily across various societies. However, whilst much attention has focused on the personal and spiritual dimensions of conversion, less has been said about the divergence between converts of conviction (those who embrace Islam owing to deeply held personal beliefs) and converts of convenience (those who convert due to external pressures and strategic interests, or to enter into a marriage with an existing Muslim). This paper examines the complex motivations behind conversion to Islam, particularly in Western, Korean, and Southeast Asian contexts. It proposes a theoretical framework to distinguish between faith-driven and circumstantially driven conversions. More explicitly, the study aims to: (a) map the range of motivations shaping conversion; (b) analyse how both converts and born-Muslims interpret sincerity, intention, and authenticity; and (c) evaluate the social, ethical, and theological implications of convenience-based conversions. Whilst acknowledging the difficulty of placing individuals into the categories of ‘conviction’ or ‘convenience,’ intention remains a central element of the Islamic tradition. This study adopts a qualitative interpretivist approach based on unstructured interviews with converts and born-Muslims, seeking to deepen understanding of the diverse trajectories of conversion, the influence of socio-political forces on religious identity, and the responsibilities of Muslim communities in engaging with both sincere and nominal converts. The findings indicate that although both conviction and convenience exist, extensive grey areas persist, particularly regarding ‘cultural Islam’ and the performance of rituals shaped more by personal habit or social custom than by deep religious commitment.